Factors associated with the behavior of breaking the chain of transmission of covid-19 in the community. - Nur Haysah; Narmi Narmi; Hasrima Hasrima; Mien Mien (KLASICS, 2023)
Coronavirus disease was first reported in Wuhan, China, precisely in 2019. WHO reports that as of 21 February 2022, there are 423,237,674 (5.4%) confirmed cases of Covid-19, representing 5,878,328 (0.07%) worldwide. Who died? The number of people positive for the new coronavirus at the work site of the Kantai Public Health Center is increasing year by year, reaching 48 and 61 from 2020 to 2021. In 2022, from January to March, he had 17 of her Covid-19 positive cases. One of the efforts to break the Covid-19 chain is to slow and stop the spread of the disease, and a key component is community engagement and support. This can be achieved if people have knowledge, perceptions, and behaviors that tend to be positive. The purpose of this study is to identify the relationship between knowledge, perceptions, and behaviors for breaking the chain of Covid-19 in society. This research method is an analytical survey and the sample size is 95 using a stratified sampling method. The survey instruments used a knowledge questionnaire by Ayu Saphira, a cognitive questionnaire by Gohel, and a modified behavioral questionnaire by Gunawan Susilawati. The results of this study showed a significant relationship between knowledge, perceptions about Covid-19, and actions to break the chain of Covid-19 in communities within the Kansai University Health Center work area with a p-value of 0.000 (<0.05). showed that there is Puskesmas recommends becoming more proactive in educating the public about Covid-19. It is also expected that the community will implement government